Cytokinin acts through the auxin influx carrier AUX1 to regulate cell elongation in the root - Street, Ian H.; Mathews, Dennis E.; Yamburkenko, Maria V.; Sorooshzadeh, Ali; John, Roshen T.; Swarup, Ranjan; Bennett, Malcolm J.; Kieber, Joseph J.; Schaller, G. Eric (Company of Biologists, 2016)
Hormonal interactions are critical for plant development. In Arabidopsis, cytokinins inhibit root growth through effects on cell proliferation and cell elongation. Here we define key mechanistic elements in a regulatory network by which cytokinin inhibits root cell elongation in concert with the hormones auxin and ethylene. The auxin importer AUX1 functions as a positive regulator of cytokinin responses in the root, AUX1 mutants specifically affecting the ability of cytokinin to inhibit cell elongation but not cell proliferation. AUX1 is required for cytokinin-dependent changes of auxin activity in the lateral root cap associated with the control of cell elongation. Cytokinin regulates root cell elongation through ethylene-dependent and independent mechanisms, both hormonal signals converging on AUX1 as a regulatory hub. An autoregulatory circuit is identified involving the control of ARR10 and AUX1 expression by cytokinin and auxin, this circuit potentially functioning as an oscillator to integrate the effects of these two hormones. Taken together, our results uncover several regulatory circuits controlling interactions of cytokinin with auxin and ethylene, and support a model in which cytokinin regulates shootward auxin transport to control cell elongation and root growth.